3D numerical modelling of concrete structural element reinforced with ribbed flat steel rebars. (December 2013) - Phan, Thanh Song; Tailhan, Jean‐Louis; Rossi, Pierre
Abstract Construction company MATIERE has developed a new type of reinforcement based on ribbed flat steel in recent years. The objective of the present work is to obtain information about the bending behaviour of RC structural elements reinforced with these ribbed flat steel bars and also about the cracking process they induce (number of cracks and crack opening), especially at the serviceability limit state. The structural element chosen for this work is a small slab‐beam (330 × 15 × 80 cm) subjected to three‐point central bending. Concurrent with this experimental study, a 3D finite element model was developed at IFSTTAR to consolidate the experimental results. It appears that the numerical modelling strategy chosen in this work is relevant for analysing both the bending behaviour of an RC structural element and its cracking process.